ECoG Beta Suppression and Modulation During Finger Extension and Flexion - Unterweger, Julian; Seeber, Martin; Zanos, Stavros; Ojemann, Jeffrey G.; Scherer, Reinhold (Frontiers in Neuroscience, 2020)
Neural oscillations originate predominantly from interacting cortical neurons and consequently reflect aspects of cortical information processing. However, their functional role is not yet fully understood and their interpretation is debatable. Amplitude modulations (AMs) in alpha (8-12~Hz), beta (13-30~Hz) and high gamma (70-150~Hz) band in invasive electrocorticogram (ECoG) and non-invasive electroencephalogram (EEG) signals change with behaviour. Alpha and beta band AMs are typically suppressed (desynchronized) during motor behaviour, while high gamma AMs highly correlate with the behaviour. These two phenomena are successfully used for functional brain mapping and brain-computer interface (BCI) applications. Recent research found movement-phase related AMs (MPA) also in high beta/low gamma (24-40 Hz) EEG rhythms. These MPAs were found by separating the suppressed AMs into sustained and dynamic components. Sustained AM components are those with frequencies that are lower than the motor behaviour. Dynamic components those with frequencies higher than the behaviour. In this paper, we study ECoG beta/low gamma band (12-30 Hz/30-42 Hz) AM during repetitive finger movements addressing the question whether or not MPAs can be found in ECoG beta band. Indeed, MPA in the 12-18 Hz and 18-24 Hz band were found. This additional information may lead to further improvements in ECoG-based prediction and reconstruction of motor behaviour by combining high gamma AM and beta band MPA.